Catálogo de los equinodermos (Echinodermata: Asteroidea y Ophiuroidea) nerítico-bentónicos del Archipiélago Cubano - Abreu-Pérez, Mercedes (2005)
Catalogue of neritic-benthonic echinoderms (Echinodermata: Asteroidea and Ophiuroidea) from the Cuban Archipelago. This is an updated taxonomic catalogue of neritic-benthonic Echinodermata (Asteroidea and Ophiuroidea) from Cuba, that includes locality, range, habitat and depth where each species is found. The species list is based on the collections of the Oceanology Institute; Havana; the “Felipe Poey” Museum (Havana University) and the National Museum of Natural History, Smithsonian Institution, Washington D.C. Specimens for those collections were captured by a variety of field techniques, narcotized with Cloral hydrate, fixed in formalin and stored in 70-80% alcohol. A total of 75 species have been identified from Cuban waters: Asteroidea (20 species) and Ophiuroidea (55 species). Rev. Biol. Trop. 53(Suppl. 3): 29-52. Epub 2006 Jan 30.